Characterization of internal flow and spray of multihole di gasoline spray using X-ray imaging and CFD - Lai, Ming Chia; Zheng, Yi; Shost, Mark; Xie, Xingbin; Matsumoto, Atsushi; Wang, Jin; Zhang, Xusheng; Moon, Seoksu; Gao, Jian; Fezzaa, Kamel; Zigan, Lars; Schmitz, Ingo; et al. (SAE Technical Papers, 2011)
Multi-hole DI injectors are being adopted in the advanced downsized DISI ICE powertrain in the automotive industry worldwide because of their robustness and cost-performance. Although their injector design and spray resembles those of DI diesel injectors, there are many basic but distinct differences due to different injection pressure and fuel properties, the sac design, lower L/D aspect ratios in the nozzle hole, closer spray-to-spray angle and hense interactions. This paper used Phase-Contrast X ray techniques to visualize the spray near a 3-hole DI gasoline research model injector exit and compared to the visible light visualization and the internal flow predictions using with multi-dimensional multi-phase CFD simulations. The results show that strong interactions of the vortex strings, cavitation, and turbulence in and near the nozzles make the multi-phase turbulent flow very complicated and dominate the near nozzle breakup mechanisms quite unlike those of diesel injections. © Copyright 2011 Society of Automotive Engineers of Japan, Inc. and SAE International.
Created from Fastlane, Scopus look-up